(untitled) (American Journal of Life Science and Innovation, 2025)
Even though a lot of research has previously been done on both C. bicolor and A. anderiana, more has to be done to assess the phytochemicals and cytotoxic potential (LC50 value) of their leaves. This work sought to identify the phytochemicals and cytotoxic activity of crude ethanolic leaf extracts of C. bicolor and A. anderiana using the A. salina (brine shrimp) Lethality Assay. During the phytochemical analysis, the leaves were boiled in distilled water and mixed with various reagents. The colors were examined to determine whether the various phytochemicals were present or not. A. salina cysts in saltwater were permitted to hatch in order to perform the cytotoxicity. The ten (10) nauplii were moved to various crude ethanolic leaf extract concentrations. The sixth (6th) hour death of nauplii was used to calculate the percent mortality rate. According to the results, the leaves of C. bicolor tested positive for flavonoids, terpenoids, tannins, and saponins. On the other hand, C. bicolor leaves tested negative for alkaloids and steroids. The presence of cardiac glycosides, terpenoids, and tannins in A. anderiana leaves was found to be positive. The leaves of A. anderiana, however, tested negative for alkaloids, steroids, flavonoids, and saponins. On the sixth (6th) hour, the LC50 value of A. anderiana crude ethanolic leaf extract was 4,712.4 μg/ml, whereas that of C. bicolor was 874,028.4 μg/ml. In the sixth hour, neither extract was cytotoxic. The phytochemicals and cytotoxic levels of the crude ethanolic leaf extracts of C. bicolor and A. anderiana were determined in this study. The findings can be applied to future research on the anti-inflammatory, antibacterial, antioxidant, and anti-diabetic bioactivities of C. bicolor and A. anderiana, which may yield non-cytotoxic medications.